(untitled) (Archive of Conferences, 2021)
Since 2020, the Samarkand State Institute of Architecture and Civil Engineering has begun and is developing new approaches to the digitalization of ancient settlements with a UNESCO protected status. The latest Smart technologies are used, which actively interact through IT systems. This is important in popularizing the cultural heritage of Uzbekistan, improving the image of the country, its ancient culture, and the use of new digital technologies reveal the hidden potential of attracting guests and will contribute to the development of the tourism industry